The “Dipylon” vases and their graves: the end of exclusivity in Early Iron age Athens: - Alexandridou, Alexandra (Revista M. Estudos sobre a morte, os mortos e o morrer, 2022)
Choosing the “Dipylon vases" as a point of departure, the present article explores the funerary practices in Athens and Attica during the middle of the eighth century and the Late Geometric I period closely associated with the date during the ninth and the second half of the eighth centuries. Rather than the funerary iconography of these vases, the context is set at the heart of the discussion. The interest is placed on the burials marked in this special way and, more importantly, on the identity of their occupants who deserved this special type of memorization, accomplished through these clay mnemata.